2018
DOI: 10.4103/0028-3886.222877
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic spectrum and prognosis in noncompressive acute transverse myelopathies: An experience of 80 patients at a tertiary care facility

Abstract: A variety of inflammatory, infective, demyelinating, and autoimmune disorders present with acute transverse myelopathy. Early institution of methylprednisolone reduces the disability in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…In a study conducted in India, Pandey S, et al concluded that early administration of methyl prednisolone reduces the morbidity in these patients. 16 Similar observation was made in our study. Delayed administration of methyl prednisolone, significant disability at presentation, and an extensive involvement of spinal cord irrespective of the cause, were associated with severe residual disability.…”
Section: Longitudinally Extensive Transverse Myelitis (Letm) Is Of Course Less Common But Clinicallysupporting
confidence: 91%
“…In a study conducted in India, Pandey S, et al concluded that early administration of methyl prednisolone reduces the morbidity in these patients. 16 Similar observation was made in our study. Delayed administration of methyl prednisolone, significant disability at presentation, and an extensive involvement of spinal cord irrespective of the cause, were associated with severe residual disability.…”
Section: Longitudinally Extensive Transverse Myelitis (Letm) Is Of Course Less Common But Clinicallysupporting
confidence: 91%
“…8,46 In this review, 13 patients (50%, of 26) reported significant motor recovery in both lower limbs after corticosteroid/MPS injection. Similar to our observation, many studies [47][48][49][50][51] reported significant motor improvement after MPS therapy.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical symptom further depends on the type of myelitis (partial or complete) and the area of the cord involved whether cervical, cervicothoracic, dorsal, dorsolumbar, or the entire length. Pandey et al 13 noted that majority ( n = 66, 82.5%) of his patients had longitudinally extensive transverse myelitis. Eleven patients had cervical myelitis, 32 patients had cervicothoracic myelitis, 24 patients had thoracic myelitis, and 13 patients had whole cord myelitis.…”
Section: Discussionmentioning
confidence: 88%
“…In South India, the prevalence of MS was noted as 8.3/100,000, and the prevalence of NMOSD which is an important cause of LETM was 2.6/100,000 among all demyelinating disorders. 11 12 In one study conducted by Pandey et al 13 in North India, they studied 80 patients out of which LETM was one of the most common presentation. Another study conducted in North East India which included 151 patients of noncompressive myelopathy with 35 years as their median age and a sex ratio of 1.4:1 showing a male predominance.…”
Section: Discussionmentioning
confidence: 99%